Study of EXAFS cumulants of FCC crystals containing n dopant atoms - Nguyen, Van Hung (H. : ĐHQGHN, 2017)
A new procedure for description and calculation of th EXAFS (Extended X-ray Absorption Fine Structure) cumulants for fee crystals containing an abitrary number n of dopant atoms have been developed. Analytical expressions for the l 8t, 2nd and 3rd cumulants have been derived.They depend on the number of dopant atoms and approach those derived by anharmonic correlated Einstein model, if all dopant atoms are taken out or replacing all the host atoms. Numerical results for Cu doped by Ni atoms based on the Morse potential show significant dependence of thermodynamic parameters of the substance on the number of dopant atoms and a reasonable agreement with experiment.